2006
DOI: 10.4161/psb.1.3.2639
|View full text |Cite
|
Sign up to set email alerts
|

Physiologically-Mediated Self/Non-Self Root Discrimination inTrifolium repenshas Mixed Effects on Plant Performance

Abstract: Recent studies suggest that plant roots can avoid competition with other roots of the same plant, but the mechanism behind this behavior is yet largely unclear and their effects on plant performance hardly studied. We grew combinations of two ramets of Trifolium repens in a single pot that were either intact, disconnected for a shorter or longer time, or that belonged to different genotypes. Interconnected ramets developed lower root length and mass than any other combination of ramets, supporting the notion t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 32 publications
(37 reference statements)
1
42
0
2
Order By: Relevance
“…roots from the same plant) from those of another plant, even when the other plant is genetically identical (Falik et al. 2003; Falik, de Kroon & Novoplansky 2006). In fact, many of the ‘Tragedy of the Commons’ root studies discussed in the previous section have been reinterpreted as the plants showing self/non‐self discrimination.…”
Section: Influence Of Neighbours On Root Responsesmentioning
confidence: 99%
“…roots from the same plant) from those of another plant, even when the other plant is genetically identical (Falik et al. 2003; Falik, de Kroon & Novoplansky 2006). In fact, many of the ‘Tragedy of the Commons’ root studies discussed in the previous section have been reinterpreted as the plants showing self/non‐self discrimination.…”
Section: Influence Of Neighbours On Root Responsesmentioning
confidence: 99%
“…Yet progress in areas such as root foraging mechanisms, or the interplay between facilitation and competition, shows that the processes involved in plant-plant competition are more complex than previously thought (Rajaniemi 2007;Chu et al 2008). An example of this is the renewed interest in the genetic determinants of intraspecific competition (for example, Falik et al 2006;Boyden et al 2008;Crutsinger et al 2008;Hughes et al 2008). In this context, a recent paper reported that plants of the annual Cakile edentula are able to identify kin in competitive settings and, more importantly, react by competing less aggressively against a close relative (Dudley & File 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Root self-discrimination and its consequences for underground competition have been reported [7,9,10,34]. However, the role of self-discrimination in above-ground interactions has largely been ignored (but see [35] for the effect of kin discrimination on above-ground traits).…”
Section: Discussionmentioning
confidence: 99%